STUDY OF WATER SORBATION OF CAA (M-34) ZEOLITIC IN ADSORBTSION MICROCALORIMETRIC DEVICE - Kokhkharov, Mirzokhid; Rahmatkariyeva , Feruza; Ergashev, Oybek; Mirjalol, Mirjalol (Educational Research in Universal Sciences, 2023)
The differential heat, isotherm, differential entropy, and thermokinetics of carbon dioxide adsorption on CaA (M-34) zeolite were measured at 303 K. Based on the results obtained; the mechanism of water adsorption in CaA (M-34) zeolite from initial filling to saturation is described in detail. The adsorption isotherm was described using the VOM equation.